2007
DOI: 10.1063/1.2766937
|View full text |Cite
|
Sign up to set email alerts
|

Novel perturbation approach for the structure factor of the attractive hard-core Yukawa fluid

Abstract: A novel perturbation approach for the structure factor S(k) of the Lennard-Jones-type Yukawa fluid with z=1.8 is presented. An approach is based on a new reference system, that is, the short-range Yukawa model with z0>z=1.8. By choosing for the reference system the value z0=6, it is shown that (i) the proposed approach for S(k) performs much better than the traditional hard-sphere reference perturbation method does; (ii) the use of an approximate mean spherical (MSA) description of the reference structure fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Nowadays, both these requirements are satisfied by the hard-core Yukawa potential. Taking into account that the analytic results for the thermodynamic functions within the mean spherical approximation are available for this fluid [25][26][27][28], in recent years it has also been used as a reference system as an alternative to the HS [29][30][31].…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, both these requirements are satisfied by the hard-core Yukawa potential. Taking into account that the analytic results for the thermodynamic functions within the mean spherical approximation are available for this fluid [25][26][27][28], in recent years it has also been used as a reference system as an alternative to the HS [29][30][31].…”
Section: Theorymentioning
confidence: 99%
“…Melynk et al [29] presented a novel perturbation approach to calculate the structure factor SðkÞ of the medium-range Yukawa fluid with z ¼ 1:8 based on the short-range Yukawa model with z 0 4 z as the reference system where z and z 0 are the decay parameters that measure the range of attraction. They showed that the proposed approach works much better than the traditional HS reference perturbation method.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11] Recently, renewed attention has been paid to hard-core attractive Yukawa fluids with short attraction range. [12][13][14][15][16][17][18][19] This interest stems mainly because they capture the most important features of real systems, such as interfacial and coexistence properties which rule many industrial processes and biological phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The short-range hard-core attractive Yukawa (HCAY) fluid has been widely used as a simple model for testing a variety of theories [1][2][3][4][5][6] and as a reference system for modeling the behavior of real fluids, such as colloidal suspensions 7,8 and protein solutions [9][10][11] . Its high popularity is due to the fact that it captures the most important features of these systems, such as coexistence and interfacial properties which rule many industrial processes and biological phenomena.…”
Section: Introductionmentioning
confidence: 99%